Orphans and other vulnerable children toolkit - International HIV/AIDS Alliance; Family Health International (Brighton, UK : International HIV/AIDS Alliance, 2006)
Contains an electronic Library of resources on supporting orphans a nd vulnerable children. These have been gathered from a wide range of o rganisations, drawing on years of experience to create a "toolkit" for others to use.
This CD-ROM is not compatible with Apple Macintosh computers.
System requirements: Adobe acrobat reader, Windows 95/98/NT/2000 or XP.
Keywords: Orphans -- Services for; Abandoned children